Provenance of the Roman basalt stone at Kotterbos (Lelystad, the Netherlands): A geoarchaeological study based on petrographic and geochemical analysis, and comparison with a synthesis of basalt stones along the northern Limes. Issue 4 (4th February 2015) - Linthout, K.
Abstract: A solitary unprocessed, 26-cm basalt stone recently found at the Roman (69 AD) site at Kotterbos (Lelystad, the Netherlands), situated 40 km north of the Limes, has been examined petrographically and geochemically. The rock is similar to previously investigated Roman basalt stones and blocks from the Limes in the province of Utrecht. All are alkali olivine basalts and basanites, which are also the dominant rock types in the nearby volcanic hinterland in Germany. On the basis of 23 criteria, including all major and minor elements plus a selection of trace elements, the Kotterbos stone correlates with a distinctive subgroup of Limes basalts. This subgroup is characterised by relatively high Mg# and low TiO2 wt% values, as opposed to the other subgroup with lower Mg# and higher TiO2 wt% values. It is argued that the high Mg#–low TiO2 subgroup and the Kotterbos basalt have common geological provenance(s). Five basalt bodies in the hinterland match the criteria of this subgroup, and might be considered as locations of provenance. Of these five, only Rolandsbogen, located next to an ideal anchorage on the west bank of the Rhine, about 12 km upstream from Bonn, can also conform to sensible Roman demands concerning effective logistics and military safety. Consequently, Rolandsbogen is the most likely site of provenance for the high Mg#–low TiO2 subgroup, which includes the Kotterbos basalt. It is argued that the Kotterbos stone is not a rock that somehow got separated from a shipment of building stones to the northern Limes; rather, it is speculated that the stone was picked up as a stray cobble near the basalt body and taken onboard a Roman vessel moored at the Rolandsbogen anchorage.